Effect of Combination of Kasturi Fruit Juice (Mangifera casturi), Vitamin E and Dha on Interleukin-6 (IL-6) Gene mRNA Expression and IL-6 Levels in Lung Inflammation of Rats (Rattus norvegicus) Due to Coal Dust Exposure - Edyson, Edyson; Natzir, Rosdiana; Subehan, Subehan; Santoso, Arif; Hardjo, Marhaen; Yustisia, Ika (Journal of Neonatal Surgery, 2025)
The respiratory tract can experience inflammation if exposed to coal pollutants. The purpose of this study was to analyze IL-6 gene mRNA expression and IL-6 levels in serum formed in experimental animals given a combination of ripe Kasturi fruit pulp juice (dose 7.8 mg/kg body weight/day dissolved in 2 ml H2O), vitamin E (dose 22 mg/kg body weight/day) and DHA (dose 60 g/kg body weight/day) exposed to coal dust at 10 pm (N10S CellMicroSievesTM BioDesign Inc. of New York, USA) given 25 mg/day/m3 in 1 hour per day for 14 days. The experimental animals were grouped into 5 groups, group 1 was the control group (no coal dust exposure and no supplements), group 2 was the coal dust exposure group, group 3 was the combination of ripe kasturi fruit juice and vitamin E with coal dust exposure, group 4 was the DHA group with coal dust exposure and group 5 was the combination of ripe kasturi fruit juice, vitamin E and DHA with coal dust exposure. Coal dust exposure was carried out for 14 days. Using the post only control design method, IL-6 gene mRNA expression and serum IL-6 levels as pro-inflammatory parameters were examined. Statistical tests of homogeneity, normality and one-way anova SPSS 25.0 were performed with = 0.05. The results showed that IL-6 gene mRNA expression and IL-6 levels in serum were established in all groups. The average IL-6 gene mRNA expression obtained by group 1 was 6.486 ± 0.272, group 2 was 10.868 ± 0.258, group 3 was 8.420 ± 0.199, group 4 was 9.096 ± 0.103 and group 5 was 7.655 ± 0.121. The average serum IL-6 level obtained by group 1 was 52.21 ± 3.02 pg/ml, group 2 was 104.93 ± 2.98 pg/ml, group 3 was 80.70 ± 2.81 pg/ml, group 4 was 90.85 ± 2.36 pg/ml and group 5 was 65.81 ± 2.54 pg/ml. Statistical tests on all groups showed homogeneity and normality (p>0.05) and one-way anova and Bonferroni post hoc found p=0.000. The conclusion of this study is that IL6 gene mRNA expression and IL-6 levels have been established. In the group given a combination of ripe Kasturi fruit juice, vitamin E, and DHA with coal dust exposure for 14 years, IL-6 gene mRNA expression and IL-6 levels in serum were found to be the lowest compared to the group exposed to coal dust and the difference was statistically significant at p=0.000.